(3GdJjSjQ aj GdeOGhGI hGdJOHjQs - (3YHO Gdedc Hf RgQ Hf YHO Gdedc, CHh eQhGf,J (B557 (3g` s
(3ChdgG (B:s
(3Efj hGdTGgO Gddg de CVY gPG GdcJGH EdG hbO dRnfj GdGVWQGQ dTOI GdYRe, hHGdCeQ Gdbhni GdLRe Edi hVYg s
(3BNQgG (B:s
(3hEPG bO CJjJ ef Gdbhd eG CQOJ EJjGfg, aCfG bGWY Gdbhd EP bO ESJJeeJg, hHGddg GdJhajb dGQH ZjQg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B241s
(3GdfSNI HgG MhGTs
(3HMhGTjgG HYV JYdjbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B303s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B71 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs